1992
DOI: 10.1007/bf01974471
|View full text |Cite
|
Sign up to set email alerts
|

Virus transmission by aphids in potato crops

Abstract: This paper reviews the contribution of vector activity and plant age to virus spread in potato crops. Determining which aphid species are vectors is particularly important for timing haulm destruction to minimize tuber infection by potato virus Y (PVY). Alate aphids of more than 30 species transmit PVY, and aphids such as Rhopalosiphum padi, that migrate in large numbers before flights of the more efficient vector, Myzus persicae, appear to be important vectors. Differences in methodology, aphid biotypes and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In contrast, spread of PLRV from within-field sources can be interrupted because of the extended post-acquisition latent period before an aphid can transmit [59][60][61] . Systemic insecticides applied at planting or plant emergence can reduce within-field spread of PLRV significantly [60][61][62][63] . Such timing gives the greatest benefit in locations where migrant aphids are rarely viruliferous.…”
Section: Chemical Controlmentioning
confidence: 99%
“…In contrast, spread of PLRV from within-field sources can be interrupted because of the extended post-acquisition latent period before an aphid can transmit [59][60][61] . Systemic insecticides applied at planting or plant emergence can reduce within-field spread of PLRV significantly [60][61][62][63] . Such timing gives the greatest benefit in locations where migrant aphids are rarely viruliferous.…”
Section: Chemical Controlmentioning
confidence: 99%
“…They are far more important and damaging as vectors of potato viruses (van Hoof, 1980;Harrington et al, 1986;Piron, 1986;de Bokx, 1987;de Bokx and van der Want, 1987;Weidemann, 1988;Flanders et al 1991;Woodford, 1992;Thomas, 1997;Stevenson, 2001;Sigvald and Hulle, 2004;King et al, 2004;Saucke and Döring, 2004;Milošević et al 2011). Potato viruses are transmitted by winged or wingless forms of both adult aphids and larvae (Robert, 1971, cit.…”
Section: Aphids As Vectors Of Potato Virusesmentioning
confidence: 99%
“…Furk et al (1990) interestingly showed that in England, R2 and R3 aphids virtually disappear during the winter from autumn-sown oil seed rape, according to winter hardness. The third need is undoubtedly to continue to develop efficient monitoring and forecasting systems, particularly in seed production areas, to assist the farmer with fixing planting dates where agronomically possible, with deciding to use granules or wait for foliar sprays according to whether the risk from aphid and virus can be forecast early before plant emergence and with estimating virus infection risks in relation to aphid species catches in different kinds of traps and plant age (Woodford, 1992), to decide for an optimum haulm killing date.…”
Section: Neth J Pi Path 98 (1992) Supplementmentioning
confidence: 99%